Stelionaat Crime from a Criminal Law Perspective and Islamic Criminal Law - Hartanto, Widi; Halim, Abdul (International Journal of Religion Education and Law, 2024)
This research was conducted to analyze how Islamic law and criminal law view land grabbing (Stelionaat). Soil is something that is essential for human life so it is a very vital object, and at the same time problems often occur in it. This research was conducted using qualitative income with primary and secondary data sources. The results of the research revealed that there were specifically no Islamic regulations regarding land grabbing, but Caliph Umar once punished someone for committing this act. Meanwhile, criminal law is generally regulated in Law no. 5 of 1960 concerning Agrarian Principles (UUPA) and government regulation Number 24 of 1997 concerning land registration.